An introduction to bond markets - Choudhry, Moorad (Chichester, West Sussex ; New York : Wiley, 2010)
"Introduction to the Bond Markets provides a comprehensive, authoritative description of the bond markets. The contents describe and define bonds within the context of the capital markets and the different types of bonds that are traded. There is also a detailed look at the analytical techniques used in the market by traders and fund managers. This new edition will be completely updated to reflect the many changes the industry has seen because of the financial crisis. In addition to a complete update, wholesale changes will be made to most chapters, taking out obsolete markets and products such as CDOs and warrants, and introducing readers to emerging markets and new issues such as Abu Dhabi issues"
Prev. ed. published: Chichester, England ; Hoboken, NJ : Wiley, c2006.
Includes bibliographical references (p.412) and index
uaj 26/04/13
Loans
Keywords: Bonds; Bond market